Phase-field Simulation of SEEDs as Nucleation Sites in Ti-6Al-4V for Electrostatic Levitation Experiments - Ueda, Yuto; Kadoi, Koei; Kushiya, Yuta; Ueno, Haruka; Mabuchi, Yuji; Hanada, Chihiro; Suzuki, Shinsuke (Proceedings of the 8\(^{th}\) International Conference on Solidification and Gravity, 2025)
This study investigated reproducing the grain refinement process of Ti-6Al-4V with TiC heterogeneous nucleation site particles in the electrostatic levitation (ESL) furnace using the phase field simulation software MICRESS®. The objective of this study is to clarify the calculation settings for simple phase field simulations such that the degree of undercooling and the frequency distribution of the grains match the ESL experimental values, and to determine the characteristics of SEEDs which act as nucleation sites using simulations. The simulation region was set at the central region of the central cross-section of the spherical ESL sample with a diameter of approximately 2 mm. To simplify the model, the region was cooled without recalescence at a constant cooling rate, R, of 171 K/s, corresponding to the ESL experiments. When simulating nucleation, a precursor of a crystal nucleus was arbitrarily set up as a fine particle “SEED”, which becomes a grain under the condition to satisfy the nucleation criterion. Six SEED-frequency distributions were modeled by extraction in the range of 1 - 200 nm. The distribution range of the SEED radii was 1-5 nm when the number of SEEDs which acted as nucleation sites matched the average number of grains in the ESL sample. Moreover, apparent interfacial mobility was fitted as a variable, which is shifted from the value derived from the physical properties. As a result, the number of grains decreased as the apparent interfacial mobility increased. Additionally, the conditions where SEEDs act as nucleation sites in the simulation were that the degree of undercooling exceeds the degree of critical undercooling of nucleation unless the SEEDs are engulfed by other neighboring grains.